Chemically Modified Poly(A) Analogs Targeting PABP: Structure Activity Relationship and Translation Inhibitory Properties. Issue 42 (10th June 2022) - Perzanowska, Olga; Smietanski, Miroslaw; Jemielity, Jacek; Kowalska, Joanna
Abstract: Poly(A)‐binding protein (PABP) is an essential element of cellular translational machinery. Recent studies have revealed that poly(A) tail modifications can modulate mRNA stability and translational potential, and that oligoadenylate‐derived PABP ligands can act as effective translational inhibitors with potential applications in pain management. Although extensive research has focused on protein‐RNA and protein‐protein interactions involving PABPs, further studies are required to examine the ligand specificity of PABP. In this study, we developed a microscale thermophoresis‐based assay to probe the interactions between PABP and oligoadenylate analogs containing different chemical modifications. Using this method, we evaluated oligoadenylate analogs modified with nucleobase, ribose, and phosphate moieties to identify modification hotspots. In addition, we determined the susceptibility of the modified oligos to CNOT7 to identify those with the potential for increased cellular stability. Consequently, we selected two enzymatically stable oligoadenylate analogs that inhibit translation in rabbit reticulocyte lysates with a higher potency than a previously reported PABP ligand. We believe that the results presented in this study and the implemented methodology can be capitalized upon in the future development of RNA‐based biological tools. Abstract : Oligonucleotide mRNA poly(A) tail analogs containing various nucleotide modifications were evaluated as binders for poly(A) binding protein (PABP) using a microscale thermophoresis‐based assay. Their susceptibility to specific degradation by CNOT7 deadenylase was also examined in order to identify best stabilizing modifications. Analogs exhibiting highest affinity and stability were tested in rabbit reticulocyte lysate system and proved to act as efficient translational inhibitors with potential applications in mRNA‐related research.